Predictable gene expression related to behavioral variation in parenting - Chris Cunningham (Behavioral Ecology, 2018)
Differential gene expression has been associated with transitions between behavioral states for a wide variety of organisms and behaviors. Heterochrony, genetic toolkits, and predictable pathways underlying behavioral transitions have been hypothesized to explain the relationship between transcription and behavioral changes. Less studied is how variation in transcription is related to variation within a behavior, and if the genes that are associated with this variation are predictable. Here, we adopt an evolutionary systems biology perspective to address 2 hypotheses relating differential expression to changes within and between behavior. We predicted fewer genes will be associated with variation within a behavior than with transitions between states, and the genes underlying variation within a behavior will represent a narrower set of biological functions. We tested for associations with parenting variation within a state with a set of genes known a priori to be differentially expressed (DE) between parenting states in the burying beetle Nicrophorus vespilloides. As predicted, we found that far fewer genes are DE related to variation within parenting. Moreover, these were not randomly distributed among categories or pathways in the gene set we tested and primarily involved genes associated with neurotransmission. We suggest that this means candidate genes will be easier to identify for associations within a behavior, as descriptions of behavioral state may include more than a single phenotype.